THE IMPLEMENTATION OF MERDEKA CURRICULUM THROUGH DIGITAL MEDIA TO ENHANCE ENGLISH SPEAKING SKILL FOR SENIOR HIGH SCHOOL STUDENTS - Kartikasari, Ririn Dwi Astuti; Hidayati, Anni Nurul; Dewi, Shinta Mardiana (ITB AAS Indonesia Surakarta, 2025)
The objectives of this research are to find out whether the use of role play technique in enhancing the students’ speaking skill, and to know the response of the students toward the implementation of the technique which is part of the Merdeka Curriculum Policy. This research was conducted at SMA N 1 Wonosari, Klaten. The study is classroom action research which consists of four stages such as: planning, acting, observing, and reflecting. The subject is the students of class XII Social 1. This class consists of 43 students. In this research, the researchers implemented role play technique in teaching speaking. The data were collected from the result observations, interviews, questionnaires, and tests. These data were compared and analyzed to get a conclusion as the result of this research. To analyze quantitative data, the research applied comparative data analysis and t-tests. To analyze qualitative data, the researchers applied interactive analysis. This research was conducted in two cycles of actions. The result of this research showed that after conducting the actions, the students’ speaking skill improved and there were a positive response toward the implementation of role play technique. This improvement could be seen from the test result and the students’ attitude during the lesson. The students’ mean score in the pre-test was 50.90. It increased to 71.52. The response of the students is good. It could be seen from the result of questionnaire. Most of them said that role play technique is interesting and help them in learning speaking. It can be concluded that the use of role play in teaching speaking can improve the students’ speaking skill. The students felt enjoyed in joining the class.